Role of serum FSH for predicting success of sperm retrieval for patients undergoing microdissection-TESE: a retrospective analysis - Kalpana, B.; Panda, Soumya Ranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The method of sperm retrieval for azoospermic patients had evolved in the recent times and micro-dissection TESE being the latest method for the same. Patient selection for TESE has always been an area of concern. Although low level of serum FSH is good indicator for successful sperm retrieval for conventional TESE, its role for micro-TESE is debatable. The primary objective of present study is to determine whether serum FSH level can predict success rate of sperm retrieval by micro-dissection TESE (micro-TESE). In addition, authors have compared the outcome of ICSI-TESE cycles between obstructive and nonobstructive azoospermia. Methods: This is a retrospective study conducted at Guru Hospital, Madurai, India between January 2014 and February 2018. Data collected from the previous hospital records. Results: Out of a total 147 azoospermic patients included in present study 68 (46.3%) were obstructive azoospermic whereas 79 (53.7%) were of nonobstructive variety. While assessing TESE- ICSI outcomes among obstructive versus nonobstructive azoospermic groups, authors found that the two groups had similar clinical pregnancy rates per transfer, chemical pregnancy rates per transfer, implantation rates, live birth rates and abortion rates per transfer. Authors also compared serum FSH level between micro TESE positive and micro-TESE negative groups. But there was no significant difference between the two groups. Authors could not find any definite correlation between serum FSH and sperm retrieval rate. Conclusions: For nonobstructive azoospermic men, TESE-ICSI provides a hope to parenting their genetically own child. Of course, before advising TESE-ICSI, nonobstructive azoospermic men should be counseled regarding the low success rate of sperm retrieval. Serum FSH level cannot predict success rate of sperm retrieval for patients undergoing micro-TESE.